Ciliates from eutrophized water in the northern Brazil and morphology of Cristigera hammeri Wilbert, 1986 (Ciliophora, Scuticociliatia) - Castro, Larissa Araguaia Monteiro de (2014)
Ciliates occur in all major aquatic and soil environments worldwide and are important links in the microbial food webs, which,along with other free-living protists, are generally overlooked in biodiversity conservation programs. In Brazil, the northernregion comprises the Brazilian Amazonia, an area widely known for its huge biodiversity. However, the diversity of ciliatesin that region is still almost unknown. As result of the present study, a total of 21 species of ciliates, distributed among 15genera, were inventoried from samples of eutrophized water collected in the city of Belém, capital of the state of Pará, one ofthe states which comprise the Brazilian Amazonia. In addition, a local population of the rare scuticociliate Cristigera hammeriis described from optical and electron microscopy observations, and its synonymy with C. pleuronemoides is rejected based onnew evidence.